Early Brain Injury Associated with Systemic Inflammation After Subarachnoid Hemorrhage - Savarraj, Jude; Parsha, Kaushik; Hergenroeder, Georgene; Ahn, Sungho; Chang, Tiffany R.; Kim, Dong H.; Choi, H. Alex (Neurocritical care, 2018)
Background Early brain injury (EBI) after aneurysmal subarachnoid hemorrhage (aSAH) is defined as brain injury occurring within 72 h of aneurysmal rupture. Although EBI is the most significant predictor of outcomes after aSAH, its underlying pathophysiology is not well understood. We hypothesize that EBI after aSAH is associated with an increase in peripheral inflammation measured by cytokine expression levels and changes in associations between cytokines. Methods aSAH patients were enrolled into a prospective observational study and were assessed for markers of EBI: global cerebral edema (GCE), subarachnoid hemorrhage early brain edema score (SEBES), and Hunt–Hess grade. Serum samples collected at ≤ 48 h of admission were analyzed using multiplex bead-based assays to determine levels of 13 pro- and anti-inflammatory cytokines. Pairwise correlation coefficients between cytokines were represented as networks. Cytokine levels and differences in correlation networks were compared between EBI groups. Results Of the 71 patients enrolled in the study, 17 (24%) subjects had GCE, 31 (44%) subjects had SEBES ≥ 3, and 21 (29%) had HH ≥ 4. IL-6 was elevated in groups with GCE, SEBES ≥ 3, and HH ≥ 4. MIP1β was independently associated with high-grade SEBES. Correlation network analysis suggests higher systematic inflammation in subjects with SEBES ≥ 3. Conclusions EBI after SAH is associated with increased levels of specific cytokines. Peripheral levels of IL-10, IL-6, and MIP1β may be important markers of EBI. Investigating systematic correlations in addition to expression levels of individual cytokines may offer deeper insight into the underlying mechanisms related to EBI.